Greening the society: Raising ecological awareness through contemporary drama course in higher education - Sahin Gulter, Isil; Tumen Akyildiz, Secil (Sage Publications Ltd, 2026)
This study investigates the potential of contemporary drama courses in higher education and the importance of integrating them into curricula to raise ecological awareness among students. Through a comprehensive needs analysis and qualitative research methodology, the students were engaged in a 9-week Contemporary Drama Course. The course featured ecological plays-Chantal Bilodeau's Sila (2015), Mike Bartlett's Earthquakes in London (2010), and Duncan Macmillan and Chris Rapley's 2071 (2014)-to explore their impact on students' perceptions and proposed actions regarding climate change. The findings revealed that the course enhanced students' understanding of climate change, categorizing their insights into physical, social, economic, and psychological implications. The most emphasized category was physical implications, highlighting changing weather patterns, water availability, ecosystems and biodiversity, and health risks. Students also proposed actions at individual and social levels, including energy conservation, sustainable transportation, waste reduction, water conservation, eco-friendly consumption, policy advocacy, community engagement, educational initiatives, and infrastructure development.
Keywords: Climate change; contemporary drama education; ecological awareness; ecological theater; higher education